2010
DOI: 10.1186/1748-5908-5-28
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge translation to fitness trainers: A systematic review

Abstract: BackgroundThis study investigates approaches for translating evidence-based knowledge for use by fitness trainers. Specific questions were: Where do fitness trainers get their evidence-based information? What types of interventions are effective for translating evidence-based knowledge for use by fitness trainers? What are the barriers and facilitators to the use of evidence-based information by fitness trainers in their practice?MethodsWe describe a systematic review of studies about knowledge translation int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 17 publications
2
18
0
2
Order By: Relevance
“…In this study, it was reported that personal fitness trainers who did not graduate with a bachelor's degree in exercise science scored 31% less on this objective measure than those personal fitness trainers holding a bachelor's degree or higher. These findings are, to some extent, consistent with systematic review evidence which shows that fitness trainers with higher levels of education are more likely to use evidence-based sources of information to inform their practice (e.g., from scientific journals), compared to those who have lower education levels, who are more likely to rely on sources such as the Internet (Stacey et al, 2010). Crucially, it was found that fitness trainers with lower levels of qualification reported difficulty in assessing the quality of the information that they accessed (particularly from the Internet) (Stacey et al, 2010).…”
Section: Issue 3: Concerns About Training and Education Provisionsupporting
confidence: 86%
“…In this study, it was reported that personal fitness trainers who did not graduate with a bachelor's degree in exercise science scored 31% less on this objective measure than those personal fitness trainers holding a bachelor's degree or higher. These findings are, to some extent, consistent with systematic review evidence which shows that fitness trainers with higher levels of education are more likely to use evidence-based sources of information to inform their practice (e.g., from scientific journals), compared to those who have lower education levels, who are more likely to rely on sources such as the Internet (Stacey et al, 2010). Crucially, it was found that fitness trainers with lower levels of qualification reported difficulty in assessing the quality of the information that they accessed (particularly from the Internet) (Stacey et al, 2010).…”
Section: Issue 3: Concerns About Training and Education Provisionsupporting
confidence: 86%
“…There was an even larger discrepancy in research use when comparing individuals with and without a post-graduate degree. Finding that individuals with a higher level of education reported greater use of research is consistent with existing literature [15]. Interventions aimed at increasing research use in organizations may need to develop different approaches (e.g.…”
Section: Identifying the Gap (Objective 1)supporting
confidence: 84%
“…For instance, fitness trainers with lower levels of education were less likely to report using evidence from scientific sources (e.g. journal article) than fitness trainers with higher levels of education [15]. Therefore, barriers, including education levels, were investigated in the current study.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Topic-specific KT reviews are indeed becoming more popular e.g., [70, 71], perhaps because of recognition that ‘one size does not fit all’ when it comes to KT [37, 53, 59]. We believe that family violence is a unique context requiring focused attention to appropriate KT practices that demonstrate value, while minimizing potential harms.…”
Section: Introductionmentioning
confidence: 99%